PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ALAT UKUR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Novita Rahayu, Ningrum; Al Bani Thariq, Ramzi; Adinanda Siswoyo, Andika (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This research aims to improve the mathematics achivement of thrid-grade studens at SDN Gili Timur 1 in the topic of measuring object length, through the use of the Problem Based Learning model combined with a staircase measuring tool. The study is motivated by the low student achievement, which is attributed to the use of ineffective teaching models and the lack of hands-on learning media. The technique applied in this reseacrch is Classroom Action Research. following the Kemmis and McTaggart model carried out in two cycles. The participants were 34 third-grade students. Data collection involved observation, interviews, written tests (pretest and posttest), and documentation. The research findings highted an enchancement in students’ learning outcomes from the pre-cycle to the second cycle. Mastery learning rose from 17.65% in the pre-cycle to 35.29% in the first cycle and 70.58% in the second cycle.The implementation of the PBL Model, supported by the staircase measuring tool, facilitated students’ understanding of length units in a concrete and contextual manner, while promoting critical thinking and teamwork in resolving problems. As a result, the Problem Based Leaning approach can be regarded as supported by the staircase measuring tool, shown to be successful in enhancing students' mathematics academic achievement in the topic of measuring object length at the elementary school level. ABSTRAK Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika siswa kelas III SDN Gili Timur 1 pada materi pengukuran panjang benda dengan menerapkan model Problem Based Learning yang didukung dengan media alat ukur tangga. Alasan utama dilaksanakannya pelaksanaan ini adalah karena tingkat pencapaian belajar siswa yang masih rendah akibat penerapan model pembelajaran yang tidak efektif dan tidak tersedianya media pembelajaran yang konkret. Metode yang diterapkan adalah Penelitian tindakan kelas menggunakan pendekatan model kemmis dan MCTaggart yang dilaksanakan dalam dua siklus. Subjek penelitian ini adalah 34 siswa kelas III. Pengumpulan data dilakukan melalui proses obsevasi, wawancara, tes tertulis (pretest dan posttest), dan dokumentasi. Hasil penelitian mengindikasikan terjadinya peningkatan hasil belajar siswa dari pra siklus ke siklus II, disertai dengan meningkatnya jumlah siswa yang mecapai ketuntasan belajar dari 17,65% pada tahap awal (pra siklus) 35,29% mengalami peningkatan pada siklus I dan 70,58% pada siklus II. Model PBL yang dibantu dengan media alat ukur tangga memudahkan siswa menguasai pemahaman terhadap satuan panjang secara konkret dan kontekstual, serta memotivasi mereka untuk mengasah pemikiran kritis dan bekerja sama untuk menyelesaikan permasalahan. Dengan demikian, kesimpulan nya adalah model Problem Based Learning yang didukung dengan media alat ukur tangga efektif dalam meningkatkan hasil belajar matematika siswa saat mempelajari topik pengukuran panjang benda di tingkat sekolah dasar.